The Role of Packaging in Influencing the Behavior of Women Living in Rural and Urban Areas when Purchasing Food Products - Yener Ögür, Aysun (Progress in Nutrition, 2022)
In the study, the role of packaging in influencing the food product purchasing behavior of women living in rural and urban areas was determined. The proportional sampling method was used to determine the sample volume. According to this method, sample size was determined as 70 in Çumra district and 70 in Selçuklu district. The role of packaging in influencing the food purchasing behavior of women living in rural and urban areas was analyzed by t-test. According to the results of the research, the socio-demographic characteristics and income status of women living in rural and urban areas were examined. 24.29% of women living in rural areas are in the 40-49 age group, while 28.57% of women living in urban areas are in the 30-39 age group. The majority of women living in rural and urban areas are primary school graduates and housewives. The average income of women living in rural areas is 659.83 per month and 18.57% of this income is spent on foodstuffs. The average income of women living in urban areas is 803.01 per month and 19.50% of this income is spent on foodstuffs. According to the results of the t-test analysis, a statistically significant difference was found regarding the role of packaging in influencing the food product purchasing behavior of women living in rural and urban areas. Firms should rely on practical steps in bringing their products to market and focus more on the knowledge of identifying the success or failure factors of products and on taking care to meet the consumer’s desires and needs, as well as on the cornerstone, starting point and end point in any productive or promotional process.